2012
DOI: 10.1002/cbic.201200206
|View full text |Cite
|
Sign up to set email alerts
|

Peptoid–Peptide Hybrid Ligands Targeting the Polo Box Domain of Polo‐Like Kinase 1

Abstract: We replaced the amino terminal Pro residue of the Plk1 polo box domain-binding 5-mer peptide (PLHSpT) with a library of N-alkyl-Gly “peptoids” and identified long-chain tethered phenyl moieties giving greater than two-orders-of-magnitude affinity enhancement. Further simplification by replacing the peptoid residue with appropriate amides gave low-nanomolar affinity N-acylated tetrapeptides. Binding of the N-terminal long-chain phenyl extension was made clear by X-ray co-crystal data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 30 publications
1
39
1
Order By: Relevance
“…Starting from the polo-box interacting protein 1 (PBIP) pT78-derived peptide PLHSpT ( 1 ), 11 we have previously reported that appending alkylphenyl groups from different positions on the peptide, including the His N(π)-position [the sequence having a (CH 2 ) 8 Ph group appended is designated as PLH*SpT ( 2a )], 12 the 4-position on the Pro residue ( 3 ) 13 and an amino-terminal N -alkyl Gly residue ( 4 ), 14 can result in up to one thousand-fold enhancement in Plk1 PBD-binding affinity (Figure 1). We found in each case that the alkylphenyl groups bind within a “cryptic binding pocket” on the PBD surface, which is defined by PBD residues Y417, Y421, Y481, L478, F482 and Y485 and revealed by rotation of the Y481 side chain (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the polo-box interacting protein 1 (PBIP) pT78-derived peptide PLHSpT ( 1 ), 11 we have previously reported that appending alkylphenyl groups from different positions on the peptide, including the His N(π)-position [the sequence having a (CH 2 ) 8 Ph group appended is designated as PLH*SpT ( 2a )], 12 the 4-position on the Pro residue ( 3 ) 13 and an amino-terminal N -alkyl Gly residue ( 4 ), 14 can result in up to one thousand-fold enhancement in Plk1 PBD-binding affinity (Figure 1). We found in each case that the alkylphenyl groups bind within a “cryptic binding pocket” on the PBD surface, which is defined by PBD residues Y417, Y421, Y481, L478, F482 and Y485 and revealed by rotation of the Y481 side chain (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the Tyr-rich hydrophobic channel has been targeted to develop the potent Plk1 PBD peptide inhibitors [1418]. But, the above channel is conserved among the three Plks (Plk1–3) [11], and as a result, a loss of Plk1 PBD monospecificity was observed [12,14,15]. In contrast to the deep understanding of the Tyr-rich hydrophobic channel, the binding nature of the pyrrolidine-binding pocket was not explored much on a molecular basis, even though there has been a high possibility of achieving monospecificity at this binding site.…”
Section: Introductionmentioning
confidence: 99%
“…7 Independently, we have found by tethering alkylphenyl groups from different positions on the shorter sequence PLHSpT ( 1 ), that we can occupy the cryptic binding pocket and achieve up to three-orders-of-magnitude enhancement in PBD-binding affinity. 8-10 Of particular note, we were able to reach the pocket from the His residue using peptides of the form PLH*SpT ( 2 ), where H* indicates the presence of a -(CH 2 ) 8 Ph group on the His N3 (π) nitrogen [ie, the His-[ N(π) -(CH 2 ) 8 Ph] (Figure 1). 8,11 This is significant for developing reduced-size binding antagonists, since this residue is at the pT-2 position, which is immediately adjacent to the “SpT” minimal recognition motif.…”
mentioning
confidence: 99%